Two new endemic species of Gorgoniidae (Cnidaria, Anthozoa, Octocorallia) from Revillagigedo Archipelago, Mexico - Olvera, Ursula; Hernández, Osvaldo; Sánchez, Carlos; Gómez-Gutiérrez, Jaime (Zootaxa, 2018)
Two new species of the genera Eugorgia and Leptogorgia were discovered while underwater collecting at the Revillagigedo Archipelago, Mexico. Sea fan species diversity and density population in these four volcanic islands is low (<12 spp.), and the possibility of endemism is high given their isolation from the mainland (403 km southwest of Cabo San Lucas, Baja California peninsula). Morphological features suggest Eugorgia wilkiei sp. nov. has a close relationship to species of the daniana group, particularly with Eugorgia multifida Verrill, 1870. However, E. wilkiei sp. nov. has densely branched irregular-pinnate colonies that grow in several simple planes or multiplanar flabelliform, and shows two distinct chromotypes (yellow or red). Leptogorgia waltonae sp. nov. is added here to the ena group because its similar in size and sclerites to Leptogorgia ena Breedy et al. 2012. However, the wart-like terminal twigs representing an enlargement of the axis (but not the coenenchyme which has the same thickness throughout the colony), 90°-angled lateral branching, and the red, purple, orange, or yellow coloration range of the colonies are the main taxonomic characters to distinguish L. waltonae sp. nov. from L. ena. Scuba diving observations in about 200 sampling locations done since 1995 to 2016 along the mexican Pacific coast, including the Gulf of California, indicate both new octocoral species are distributed only at Revillagigedo islands. Revillagigedo Archipelago is surrounded by oligotrophic oceanic waters, strong seawater currents, and relatively frequent hurricane perturbations that favor small or robust, and hard and resistant sea fan colonies, low-species diversity, and low-population density. These factors may enhance speciation processes supporting the comparatively high endemism of the islands benthic fauna as well.